Efficacy of tramadol as an adjuvant to bupivacaine for caudal analgesia in children: a randomised controlled trial - Regmi, Upendra Krishna; Sapkota, Shanta (Journal of Society of Anesthesiologists of Nepal, 2017)
Background: The goal of postoperative analgesia is to minimise pain with least possible side effects and in our setting be as cost effective as possible. In children, caudal anaesthesia is typically combined with general anaesthesia for intraoperative and postoperative analgesia. Adjuvants can be added to local anaesthetics for prolonging the duration of analgesia. This study was done to find out the duration of analgesia of caudal Bupivacaine in combination with Tramadol. Methods: This prospective, randomised, double-blind, comparative study was done by taking a total of 60 patients, aged between 2 to 7 years undergoing elective lower abdominal, urological and lower extremity surgeries. The patients were randomized to group A (n=30) receiving 1 ml/kg of 0.25% bupivacaine and group B (n=30) receiving 1 ml/kg of 0.25% bupivacaine plus 1mg/kg of tramadol caudally. Duration of analgesia, hemodynamic responses and adverse effects were noted and analysed. Results: Thirty patients in both groups were comparable with regard to demographic data and hemodynamic response and were statistically non-significant (P>0.05). It was observed that the mean duration of analgesia was significantly longer in group B (467.5±164.5 min versus 240.5±69.4 min, P<0.001). One patient in each group had postoperative vomiting. Conclusion: Tramadol 1mg/kg as an adjuvant to bupivacaine 0.25% for caudal analgesia in children is effective in increasing the duration of analgesia without an increase of adverse effects.